Perceptions Towards No Single-Use Plastic Policy: The Case of Casual Dining Restaurants - Vicente, Khrisna; Vicente, Ruth; Mapalad, Gina; Faminialan, Janine; Formento, Sisa; Fadera, Irene; Eledia, Olga (Romblon State University Research Journal, 2023)
Environmental challenges are becoming a never-ending source of study. Many nations are currently focusing on environmentally friendly policies. In the Philippines, Republic Act No. 9003 established an ecological solid waste management program. In 2020, the municipality of Odiongan, Romblon enforced the "no single-use plastics" ordinance in all businesses, including restaurants. The goal of this research was to discover local green rules that apply to casual dining restaurant businesses. It also sought to establish how participants felt about the local government’s green programs and identified the numerous green efforts and practices of selected restaurants as well as the impact of green policies on their operations as viewed by the owners/managers. The descriptive-qualitative approach using interview as a data collection method was used. Results show that the town of Odiongan is facing several challenges in properly implementing its green initiatives such as the availability and durability of low-cost alternative packaging materials. The policy on "no single-use plastics" needs to be understood more by casual dining restaurant owners and the general public.